إثارة الدفع بعدم الدستورية أمام الجهات القضائية الجزائية في الجزائر - حنان, قده; فايزة, جروني (University of Eloued جامعة الوادي, 2020)
المقال إثارة الدفع بعدم الدستورية أمام الجهات القضائية الجزائية؛إذ يكتس ي هذا الموضوع أهمية بالغة تتجلى في أهمية هذه الآلية بيد المتهم أو محاميه؛حتى يتمكن من حماية حقوقه وحرياتهالتي يكفلها الدستور.ومعالجتنا لهذا الموضوع هدفها توضيح توقيت إثارة الدفع بعدم الدستورية خلال سير الدعوى العمومية، والتعرض لمبررات استثناء محكمة الجنايات الابتدائية من الجهات القضائية الجزائية التي يمكن إثارة الدفع بعدم الدستورية أمامها، حيثوضحنا فيهذه الدراسة أن الدفع بعدم الدستورية يمكن إثارته أثناء التحقيق الجزائي أمام غرفة الاتهام، كما يمكن إثارته أمام باقي الجهات القضائية الجزائية باستثناء محكمة الجنايات الابتدائية؛نظرا لخصوصية الإجراءات المتبعة أمامها. This article discusses pleading the unconstitutionality of a law before criminal judicial authorities. The importance of this topic is reflected in the value of this mechanism when used by the defendant or their lawyer so that they can protect their rights and freedoms guaranteed by the Constitution. By dealing with this topic, we aim to clarify the timing of pleading the unconstitutionality of a law during the course of the public case, the discussion of the justifications underlying the exception of the Court of First Instance from the criminal judicial bodies which may itself be the host of the plea of unconstitutionality. This study concludes that the claim of unconstitutionality can be raised during the criminal investigation before the indictment chamber, and it can also be raised in front of the rest of the judicial authorities with the exception of criminal offenses Court of First Instance, given the specificity of the procedure undertaken before it.
مجلد11، عدد1
Keywords: بعدم الدستورية؛التحريات الجزائية؛التحقيق القضائي؛حقوق وحريات المتهم؛محكمة الجنايات الابتدائية؛الجهات القضائية الجزائية; Pleading the unconstitutionality of law; Criminal investigations; Judicial investigation; Rights and freedoms of the defendant; Court of First Instance; criminal judicial authorities